2001
DOI: 10.1016/s0893-133x(00)00205-0
|View full text |Cite
|
Sign up to set email alerts
|

Anxiogenic-Like Effects Limit Rewarding Effects of Cocaine in BALB/cByJ Mice

Abstract: Previous studies have reported intravenous cocaine selfadministration behavior in several strains of mice with the exception of BALB/cByJ, a strain considered a mouse model of high emotional reactivity. The present experiments further investigated acquisition of self-administration in BALB/cByJ mice using a low dose and a habituation session. Following evidence of an initial drug-seeking behavior, we observed a progressive decline of intravenous self-administration. Pretreatment with diazepam (0.5 mg/ kg, IP),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 82 publications
5
26
0
Order By: Relevance
“…This gradual extinction/suppression of cocaine self-administration was reversed by diazepam pretreatment, and the results were interpreted by the authors to support the hypothesis that cocaine has anxiogenic effects. The results of the present experiment concur with this hypothesis, and combine with those of David et al (2001) to suggest that individuals with high trait levels of anxiety are more sensitive to cocaine's aversive effects.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This gradual extinction/suppression of cocaine self-administration was reversed by diazepam pretreatment, and the results were interpreted by the authors to support the hypothesis that cocaine has anxiogenic effects. The results of the present experiment concur with this hypothesis, and combine with those of David et al (2001) to suggest that individuals with high trait levels of anxiety are more sensitive to cocaine's aversive effects.…”
Section: Discussionsupporting
confidence: 89%
“…David et al (2001) successfully trained these mice to nose-poke for low doses of i.v. (0.2 mg kg −1 infusion −1 ) or intraaccumbens (10 ng) cocaine infusions, but the mice gradually extinguished responding, and exhibited retreat behaviors reminiscent of those reported by Ettenberg and Geist (1991).…”
Section: Discussionmentioning
confidence: 99%
“…Data are expressed as the mean ± SEM of the time taken to complete the first active (a and c) or inactive (b and d) lever press for each SA session cocaine in rats (Ettenberg et al 1999) may only be evident in those individuals characterized as LA on the EPM (Rogerio and Takahashi 1992). It has also been suggested that these effects could limit the rewarding properties of the drug (David et al 2001), with the implication being that the relative insensitivity of HA rats to cocaine-associated anxiogenesis could render them more vulnerable to escalation of drug intake. In the present study, however, there were no differences between HA and LA rats with respect to latencies to the first active lever press of each SA session, which has been taken to be an index of sensitivity to the anxiogenic properties of cocaine experienced in previous sessions (Maier et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…anxiety, paranoia, nausea, hypertension). In addition to its well-documented rewarding and locomotor activating effects in rodents, cocaine also induces anxiety-like behavior that can be reversed by administration of typical anxiolytic drugs, such as diazepam (1)(2)(3)(4)(5)(6)(7). Whereas cocaine-induced reward has been studied extensively, less is known about the processes underlying the negative behavioral states associated with acute administration of the drug.…”
Section: Introductionmentioning
confidence: 99%